A highly stable MnII phosphonate as a highly efficient catalyst for CO2 fixation under ambient conditions. Issue 14 (30th January 2018) - Yang, Yang; Gao, Chao-Ying; Tian, Hong-Rui; Ai, Jing; Min, Xue; Sun, Zhong-Ming
Abstract : A highly stable microporous Mn II phosphonate is rationally designed and it exhibits highly efficient performance in the context of CO2 chemical conversion into cyclic carbonates under ambient conditions. Abstract : With coordinatively unsaturated metal centers decorating the channel walls, a Mn II phosphonate exhibits highly efficient and substrate size-selective catalysis in the context of CO2 chemical conversion into cyclic carbonates under 1 atm pressure and at room temperature, proving to be a promising heterogeneous catalyst in an eco-friendly and energy efficient way.